ANALISIS KANDUNGAN KADAR LOGAM BERAT TIMBAL (Pb) DI PERAIRAN PULAU PAHAWANG DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Rosa Pane, Elfira; Nisa, Khoirun; Sunarsih, Tri (Jurnal Multidisipliner Kapalamada, 2024)
This study is entitled Analysis of the Content of Heavy Metal Levels of Lead (Pb) in the Waters of Pahawang Island by Atomic Absorption Spectrophotometry Method (SSA). The problem to be studied is how much Pb metal content is in the waters of Pahawang Island analyzed by SSA? The purpose is to determine the levels of Pb metal at 4 points around the island of pahawang whether in accordance with existing quality standards. The data analysis method is to use simple regression. The results showed that the SSA spectrophotometer, lead levels in large kelagian, small kelagian, and large pahawang showed no lead metal content (Pb), but there were levels of lead metal (Pb) in seawater around the pier which amounted to 0.016 mg/L, which is still within safe limits in accordance with the Decree of the Minister of Environment No. 51 of 2004 which has been revised in No. 179 of 2004 concerning Seawater Quality Standards for Pb content which is 0.05 mg/L.